2014
DOI: 10.1111/1567-1364.12170
|View full text |Cite
|
Sign up to set email alerts
|

Variations in mitochondrial membrane potential correlate with malic acid production by natural isolates ofSaccharomyces cerevisiaesake strains

Abstract: Research on the relationship between mitochondrial membrane potential and fermentation profile is being intensely pursued because of the potential for developing advanced fermentation technologies. In the present study, we isolated naturally occurring strains of yeast from sake mash that produce high levels of malic acid and demonstrate that variations in mitochondrial membrane potential correlate with malic acid production. To define the underlying biochemical mechanism, we determined the activities of enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…For example, it was reported that the mitochondrial activity of yeast used for brewing Japanese sake affected malate and succinate production during alcoholic fermentation (32,33). Moreover, Kyokai 7, yeast used for brewing Japanese sake, displayed greater the oxidative TCA cycle activity and the mitochondrial activity than the laboratory strain according to 13 C-MFA and mitochondrial morphology (22).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was reported that the mitochondrial activity of yeast used for brewing Japanese sake affected malate and succinate production during alcoholic fermentation (32,33). Moreover, Kyokai 7, yeast used for brewing Japanese sake, displayed greater the oxidative TCA cycle activity and the mitochondrial activity than the laboratory strain according to 13 C-MFA and mitochondrial morphology (22).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that this pathway is occurring in eukaryotes such Aspergillus flavus, Aspergillus oryzae, Candida glabrata, Penicillium spp. and Saccharomyces cerevisiae and in the prokaryotes Bacillus subtilis and a metabolically engineered strain of Escherichia coli [2,[12][13][14]. In S. cerevisiae, it was shown that pyruvate carboxylase and malate dehydrogenase activities were elevated in a strain exhibiting elevated malic acid production [13].…”
Section: Pathways Of Malic Acid Biosynthesismentioning
confidence: 99%
“…and Saccharomyces cerevisiae and in the prokaryotes Bacillus subtilis and a metabolically engineered strain of Escherichia coli [2,[12][13][14]. In S. cerevisiae, it was shown that pyruvate carboxylase and malate dehydrogenase activities were elevated in a strain exhibiting elevated malic acid production [13]. In a strain of the thermophilic soil bacterium, Thermobifida fusca muC, phosphoenolpyruvate is converted to oxaloacetate by phosphoenolpyruvate carboxylase and the oxaloacetate reduced to malate by malate dehydrogenase [5].…”
Section: Pathways Of Malic Acid Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Malate is one of major organic acids in sake that confers a desirable fresh, sour taste (1,2). Various methods have been developed for breeding high malate-producing yeast strains by mutagenesis (3)(4)(5)(6)(7), and many studies have described the mechanistic bases for their high-malate phenotype (8)(9)(10)(11). Various methods have been developed for breeding high malate-producing yeast strains by mutagenesis (3)(4)(5)(6)(7), and many studies have described the mechanistic bases for their high-malate phenotype (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%